Addressing the water conflict between agriculture and ecosystems under environmental flow regulation: An integrated modeling study. (December 2020) - Zheng, Yi; Tian, Yong; Du, Erhu; Han, Feng; Wu, Yajie; Zheng, Chunmiao; Li, Xin
Abstract: Modeling agriculture-impacted hydrological processes remains a challenge, as information on irrigation activities is often insufficient. This study developed modules for emulating high-resolution irrigation activities and representing water management policies in integrated hydrologic modeling. The new modeling approach was implemented in China's second largest endorheic river basin with intensive irrigation and exemplary environmental flow regulation. Pumping management is found to impact the hydrological regime at the basin scale and modulate the tradeoff between ecological services and agriculture. Limiting the groundwater level decline within 1 m would lead to a 3.9% decrease in cropland evapotranspiration in the middle basin and a 1.5% increase in the environmental flow towards the lower basin. Environmental flow regulation and pumping management have both synergistic and offset effects, reflecting a complex water-agriculture-ecosystem nexus in this basin. This modeling study suggests heterogeneous and dynamic groundwater management policies in water-limited areas and unravels threshold effects in the policies. Highlights: A new module for hydrologic models to emulate high-resolution irrigation activities. A typical tradeoff between ecosystems and agriculture tuned by pumping management. Diversion regulation and pumping control have both synergistic and offset effects. Heterogeneous and dynamic groundwater management policies are preferred. Threshold effects are observed for the groundwater management policy.